The Settlement of Election Disputes by Bawaslu Reviewed from the Indonesian Justice System - Jamaluddin, Jamaluddin (International Journal Labs, 2022)
Background: In order to bring about a government that is just, prosperous, and still stands on a democratic government, a country must be based on the implementation of elections or elections that are fair, honest, free, and secret from the principles of good governance. Aim: This article aims to explore the settlement of election disputes conducted by Bawaslu through the Indonesian justice system’s view. Method: This research is a normative legal study by reviewing or analyzing primary and secondary data by understanding the law as a device or positive norm in the legal system that regulates human life. Findings: The duration of the settlement of the case given to Bawaslu becomes a thing that is considered less wise in the effectiveness of the settlement of words and this is different from MK which is quite the opposite.